Right atrial deformation through speckle tracking echocardiography and feature tracking CMR - Rai, ABS (2014)
The right atrium (RA) plays a vital role in the electromechanical regulation of the heart. Various invasive and non-invasive techniques have been used to elucidate right atrial structure and function. One such novel technique is speckle-tracking echocardiography (STE). Speckle tracking-derived deformation is a relatively new parameter, which is less dependent on loading conditions. STE tracks acoustic scatters (speckles) of myocardium, frame by frame, to calculate the strain or deformation indices of the myocardium. The right atrium is a relatively neglected chamber as it is mostly studied for assessment of atrial mass lesions, congenital and acquired valve lesions and for electro physiological studies. However, its role in the systolic and diastolic function of the right ventricle of the heart has been less explored. I have adapted the STE technique, designed for left ventricular analysis, for use in the right atrial analysis. I undertook a reproducibility study for right atrial deformation parameters and defined normal reference ranges for longitudinal deformation parameters. I have found the analysis approach used generates similar values to those reported in the limited number of previous studies on right atrial STE. I then compared STE derived strain with cardiovascular magnetic resonance feature tracking derived measures of right atrial strain and found moderate agreement between the two techniques. Finally, I investigated whether there are differences in right atrial longitudinal deformation parameters in different patient disease groups. I studied those with Heart Failure with Normal Ejection Fraction (HFNEF) and found a decrease in right atrial function. Whereas, in another cohort of patients with Rheumatoid Arthritis (RhA) there was no statistical difference compared to healthy controls. This thesis therefore demonstrates the feasibility of using STE to measure right atrial strain and provides evidence that right atrial strain does vary in certain disease conditions.